Does Household Worklessness Explain Ireland’s High Working-Age Market Income Inequality? - Nolan, Brian; Maître, Bertrand (The Economic and Social Review, 2021)
Ireland has a particularly high level of inequality in incomes from the market, before redistribution by transfers and direct taxes, and also a very high level of household joblessness. How much does the latter serve to explain the former? We assess this by comparing Ireland in depth with five comparator countries: France, Germany, Spain, Sweden and the UK. Decomposition of the Gini coefficient by income source shows the dominant role played by income from labour in market income inequality in all these countries. Decomposition of Generalised Entropy measures and counterfactual shift-share exercises based on them show that Ireland’s high proportion of working-age households with no earner is indeed an important contributor to its ranking in terms of market income inequality. However, relatively high levels of dispersion in earnings within one-earner and two-earner households also contribute and their drivers need to be better understood.